Re-activation of HIF signalling pathway in the epicardium improves heart regeneration after myocardial infarction. (10th June 2022) - Gamen, E; Price, EL; Pezzolla, D; De Villiers, C; Gunadasa-Rohling, M; Salama, R; Mole, DR; Bishop, T; Pugh, CW; Choudhury, RP; Carr, CA; Vieira, JM; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation Background: In mouse, cardiac regenerative capacity is maintained for the first week after birth but lost thereafter. Reactivation of this process holds great therapeutic potential, however, the molecular pathways that might be targeted to extend neonatal regeneration remain elusive. Here, we explore a role for hypoxia inducible factor (HIF) family of transcription factors on the regulation of epicardial activity which is essential for cardiac response to injury. Purpose: HIF signalling might be involved in the quiescence of the epicardium observed in the first week of life. Thus, HIF stabilisation may induce epicardial re-activation and extend the 7-day regenerative window in a neonate mouse model of myocardial infarction (MI). Methods: We analysed epicardial expression of HIF signalling during embryonic development, and in a regenerative post-natal day 1 (P1) versus non-regenerative (P7) mouse model by single cell RNA-sequencing. Next, we established in vitro epicardial explants to confirm the role of HIF signalling in epicardial activation, and finally we induced MI by permanent ligation of the proximal left anterior descending (LAD) coronary artery in P7 mice to test weather HIF signalling re-activation improved heart regeneration in a non-regenerative model. Results: Expression of both HIF-1α and HIF-2α is very pronounced at early stages of heart development and gradually decreases throughout gestation. The epicardium preferentially expresses HIF-1α by embryonic day (E) 16.5. Postnatally, GO term analysis showed an enrichment of hypoxia-related pathways in P1 compared to P7 hearts, largely in the epicardial cell population. Accordingly, expression of Phd2, encoding for the main suppressor of HIF signalling, was enriched in P7 derived epicardial cells. Notably, the increase in Phd2 levels coincided with a clear reduction in the expression of Wilms' tumour 1 (Wt1) in P7 versus P1 hearts, a key player in the epicardial activation. In vitro studies on epicardial explants confirmed regulation of WT1 expression and migration capacity following genetical and pharmacological modulation of HIF signalling. Finally, in vivo targeting of PHD enzymes through pharmacological inhibition with clinically approved drugs in a neonatal mouse model of MI led to prolonged epicardial activation, increased vascularisation, augmented infarct resolution and preserved cardiac function up to 3 weeks after injury. Conclusions: Together, these findings show that modulation of HIF signalling can regulate epicardial activity and improve heart regeneration capacity beyond the 7-day regenerative window and may represent a viable therapeutic strategy for treating ischaemic heart disease.